The environment - "Allaby" (Horus: London, 1996)
In the pages of this book we discover how -- from the soil beneath out feet, to the clouds above our heads -- the environment is a fascinating world of natural cycles, systems and life processes. Lavish illustrations show how communities of plants and animals live together in their surroundings. Combined with lucid text, they explain how the environment achieves its own balance, a balance easily upset by some human activities
Keywords: Climatic changes